Postbiotics—A Revolution Engineering Symbiotics ofInanimate microorganisms and their components - ółkiewicz, Jakub Z˙; Marzec, Aleksandra; Phia, Wong Jest (International Journal of Scientific Research and Management (IJSRM), 2024)
As an imbalance in the intestinal microbiota can lead to the development of several diseases (e.g., type 1 diabetes, cancer, among others), the use of prebiotics, probiotics, and postbiotics to alter the gut microbiome has attracted recent interest. Postbiotics include any substance released by or produced through the metabolic activity of the microorganism, which exerts a beneficial effect on the host, directly or indirectly. As postbiotics do not contain live microorganisms, the risks associated with their intake are minimized. Here, we provided a critical review of postbiotics described in the literature, including their mechanisms of action, clinical characteristics, and potential therapeutic applications. We detailed the pleiotropic effects of postbiotics, including their immunomodulatory, anti-inflammatory, antioxidant, and anti-cancer properties. Although the use of postbiotics is an attractive strategy for altering the microbiome, further study into its efficacy and safety is warranted.